New Antiarrhythmic Agent to Stabilize Functional Activity of Rat Heart Sinus Node Cardiomyocytes - Ruben S. Mirzoyan; Antonina I. Turilova; Tamara S. Gan'shina; Nina I. Avdyunina; Boris M. Pyatin; Alexandra D. Meshchaninova; Anastasia S. Rodina; Olga Yu. Shagaleeva; Valentin I. Zolotarev; Pavel V. Sutyagin (Belgorod National Research University, 2020)
Introduction: The aim of this study was to explore the antiarrhythmic activity of the new antiarrhythmic drug, succinic acid ester of 5-hydroxyadamantane-2-one (ADK-1110) and its effect on the functional activity of rat heart sinus node. Materials and methods: Experiments were performed on 80 non-linear white awake male rats weighing 200 g, using calcium chloride and aconitine arrhythmia models. The ECG was recorded from all the animals in the II standard lead before the start of the experiment. The effect of ADK-1110 on the electrical activity characteristics of rat heart sinus node pacemakers in vitro was studied on 26 outbred Wistar rats of both sexes with a body weight of 160 to 200 g, using the microelectrode technique. Results and discussion: The compound significantly exceeds the known reference drugs in terms of the antiarrhythmic index. The agent also surpasses our previously proposed adamantane derivative ADK-1100 on calcium chloride model and is not inferior to the aconitine one. The electrophysiological analysis of the sinus node pacemaker cardiomyocytes characteristics in vitro under the influence of ADK-1110 revealed that the compound expands the area occupied by true pacemakers. Discussion: The obtained data indicate the presence of properties of antiarrhythmics of classes I, III, and IV in ADK-1110. The indicated functional remodeling stabilizes the functional activity of the central part of the sinus node. Conclusion: ADK-1110 stabilizes the functional activity of the central part of the sinus node. ADK-1110 also has a cerebrovascular anti-ischemic property.